Availability of the Sangatta Pelangi Hill Slide Using Geoelectric Correlation on the Borlog - Efendi, Aco Wahyudi (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2023)
The earth's surface moves downward from a point in a process known as land subsidence, which causes the elevation of the ground surface to drop or become lower than it was. The geoelectric technique is one way to investigate soil. Depending on the electrical characteristics of the rock, this technique is one of the geophysical exploration methods that can give a generalized (map) of a rock layer or formation and the depth of the rock layers. The goals of this study were to model landslide behavior and identify the soil layers using geoelectric data. The rock or hard soil zone has a high resistivity rating based on geoelectricity. As a result, evidence of topsoil to clay may be seen in Trace 1's rock or hard soil zones, which range in depth from 18.5 to 24.9 tie points and 40 to 120 tie points, respectively. The soil layer is unidirectional and uniform. This geoelectrical value is linear with the results of a soil survey performed using the drilling method, i.e., the soil properties are quite sturdy and strong at a depth of 10–20 meters, with NSPT at a depth of 10–17 and increases at that depth. than 20 m at NSPT 60, and because it has reached twice NSPT 60, this can be considered real rock.